Multiscale urban air pollution modelling: towards healthier cities - Silveira, Carlos Miguel de Sousa (2020)
Ambient air pollution is nowadays a serious public health problem worldwide, especially in urban areas due to high population density and intense anthropogenic activity. Among the main urban air pollution sources, the road traffic sector is one of the major concerns and the largest contributor to nitrogen dioxide (NO2) concentrations, though regional background chemical conditions must also be considered. In this context, the use of modelling tools is crucial to understand atmospheric and social dynamics in multiple scales, as well as to support in defining the best air quality improvement strategies. The main objective of this thesis is to develop and apply a multiscale modelling system able to simulate air quality and health impacts in cities. For this purpose, the modair4health multiscale air quality and health risk modelling system was developed and operationalized. It includes the online model WRF-Chem, which provides air quality and meteorological fields from regional to urban scales, and the Computational Fluid Dynamics (CFD) model VADIS, which uses the urban WRF-Chem outputs to calculate flows and dispersion of traffic emissions-related air pollutants in urban built-up areas. A health module, based on linear and non-linear World Health Organization approaches, was also integrated in modair4health to assess the health impacts resulting from air quality changes, and the overall health damage costs are calculated based on economic studies. The application and assessment of the modair4health system allowed to identify the most appropriate configurations and input data, which were used to apply the system over the case study testing air quality improvement scenarios. One of the busiest road traffic areas of the city of Coimbra (Fernão de Magalhães Avenue) in Portugal was selected as case study. The application considered a 4 domains setup: three nested domains (25, 5 and 1 km2 resolutions) for the WRF-Chem, and the 4th domain (4 m2 resolution) over the target local study area and NO2 for the VADIS. WRF-Chem was applied along the year 2015 and VADIS was simulating two particular periods: one week in winter and another one in summer. Short-term health impacts were estimated and the non-linear approach led to lower health outcomes that seem better adjusted to the local reality. Finally, to assess the modair4health capabilities for decision-making support, two traffic management scenarios were tested over the case study: replacement of 50% of the vehicle fleet below EURO 4 by electric vehicles (ELEC), and introduction of a Low Emission Zone (LEZ). Air quality and health positive impacts were higher for the ELEC scenario. This study represents a scientific advance in multiscale air quality and health modelling. The modair4health system can be easily adapted and applied to other simulation domains, providing urban air pollution levels and subsequent health impacts for different case studies and supporting the assessment of air pollution control policies.